2008
DOI: 10.5194/acp-8-5649-2008
|View full text |Cite
|
Sign up to set email alerts
|

The influence of chemical composition and mixing state of Los Angeles urban aerosol on CCN number and cloud properties

Abstract: Abstract.The relationship between cloud condensation nuclei (CCN) number and the physical and chemical properties of the atmospheric aerosol distribution is explored for a polluted urban data set from the Study of Organic Aerosols at Riverside I (SOAR-1) campaign conducted at Riverside, California, USA during summer 2005. The mixing state and, to a lesser degree, the average chemical composition are shown to be important parameters in determining the activation properties of those particles around the critical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
175
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(197 citation statements)
references
References 105 publications
(117 reference statements)
17
175
5
Order By: Relevance
“…The size distribution of LOA supports the interpretation that this component is locally produced, probably by industrial combustion. In addition, these size distributions are less noisy and likely more robust than those obtained previously by tracer methods, and could be used for future cloud condensation nuclei (CCN) and hygroscopicity studies (Cubison et al, 2008;Gunthe et al, 2009;.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The size distribution of LOA supports the interpretation that this component is locally produced, probably by industrial combustion. In addition, these size distributions are less noisy and likely more robust than those obtained previously by tracer methods, and could be used for future cloud condensation nuclei (CCN) and hygroscopicity studies (Cubison et al, 2008;Gunthe et al, 2009;.…”
Section: Discussionmentioning
confidence: 99%
“…First, we can compare the static size distributions from the 3-vector model with the average size distributions from the vector-matrix model. Second, we can compare the dynamic diurnal average size distributions from the vector-matrix to size distributions estimated from tracer m/z's Cubison et al, 2008;Wang et al, 2010).…”
Section: Evaluation Of the Assumptions Of The 3-vector Modelmentioning
confidence: 99%
“…In the case of absorbed particles, not only the mass concentration but also their composition, the size distribution of both aerosol particles and cloud droplets, and the mixing state (external; internal homogeneous; core/shell) have a strong effect on the interaction with solar radiation Cubison et al, 2008;Péré et al, 2009;Jacobson, 2012).…”
Section: Radiative Effects Of Gases and Aerosolsmentioning
confidence: 99%
“…Broekhuizen et al (2006) and Cubison et al (2008) both show evidence that CCN closure can be improved with knowledge of size-dependent composition. Cubison et al (2008) also found that assumptions about the aerosol mixing state (internal or external) can adversely impact CCN predictions. They sampled aerosol near Los Angeles, California in an urban airmass.…”
Section: Ccn Closure Reviewmentioning
confidence: 99%
“…It was developed by Roberts and Nenes (2005) and has been used in many field programs and laboratory studies since its introduction (e.g. Medina et al, 2007;Ervens et al, 2007;Cubison et al, 2008;Quinn et al, 2008;Gunthe et al, 2009). Supersaturation (SS) is maintained in the CCN-100 4306 D. S. Ward and W. R. Cotton: Cold and transition season by imposing a tightly controlled temperature gradient on the sheath/sample flow within a moist growth chamber.…”
Section: Methodsmentioning
confidence: 99%